Telerehabilitation versus face-to-face physical therapy for middle-aged patients with degenerative meniscal tear in China: a non-inferiority randomized controlled trial - He, Jiye; Xu, Caiqi; Huang, Lihua; Wang, Hui; Lu, Shengdi (Journal of rehabilitation medicine, 2025)
Objective: This study aimed to compare the effectiveness of telerehabilitation to traditional face-to-face physical therapy for patients with degenerative meniscal tears in Shanghai, China. Design: A two-arm, single-blinded, randomized controlled trial was conducted across two hospitals in Shanghai, China Subjects/Patients: Participants with clinically diagnosed degenerative meniscal tears were randomly assigned to either the telerehabilitation group or the face-to-face physical therapy group. Methods: Both groups underwent a 12-week intervention. Participants in telerehabilitation group used a digital platform for remote physical therapy, while participants in physical therapy group received traditional clinic-based rehabilitation. A predefined non-inferiority margin of 10 points on the Knee Injury and Osteoarthritis Outcome Score (KOOS) was applied to determine clinical equivalence between the interventions. Results: Both groups demonstrated significant improvements in knee function and quality of life, with no significant differences in the KOOS, SF-36, or functional tests at any time point (p > 0.05). Both groups had high adherence rates, with no significant differences in exercise completion or satisfaction scores. The TELE group had a significantly lower total cost compared to the PT group (p < 0.001), demonstrating greater cost-effectiveness. Conclusion: Telerehabilitation was found to be clinically non-inferior to face-to-face physical therapy for improving knee function, pain, and quality of life in patients with degenerative meniscal tears. It offered significant cost savings, making it a cost-effective alternative to traditional in-person rehabilitation.